(untitled) (Tanzania Journal for Population studies and Development, 2015)
This article seeks to explore Ama Ata Aidoo’s (2002) work for the purpose of interrogating how African feminists and/or women writers represent challenges facing African women, as well as suggested or implied solutions to their problems. The analysis interprets the stories ‘Lice’, ‘Comparisons’, ‘The Girl Who Can’, and ‘Heavy Moments’ in an attempt to identify elements of women’s oppression under patriarchy rule, and to what extent women can challenge that system. Although some female characters in these stories have proved to challenge the system and subverted men’s hierarchy, the underlying implications as to what a woman ought to do to overcome the oppression leaves a lot to be desired. The article attempts to disentangle Aidoo’s narratives, and in the process of disentangling it demonstrates newly established feminist constructs that ought to be subverted.